The Claims and the Use of Land by Local Communities and by the FMU of 50 Kota District in Jorong Landai, Nagari Harau, 50 Kota District, West Sumatra, Indonesia - Uswatul Hasana; Mahdi; Wilson Novarino; Farid Azel (International Journal of Science and Society, 2020)
Forest Management Unit (FMU) of 50 Kota district, whose appointment by the Decree of the Minister of Forestry No. 44 / Menhut-II / 2012 on February 2, located in the 50 Kota district of West Sumatra Province, Indonesia with wide ± 117 552 ha. FMU of 50 Kota district try to make some forest management plans in certain areas such as the development for forest conservation function, production function and protected function. Local communities in 50 Kota district, some of them still dependent on the forest, and Location FMU of 50 Kota district is in the West Sumatera, that famous with the Minangkabau people with their long-existing village management system, known as Nagari. The Nagari established, to settle disputes based on customary principles as well as to protect the rights of the community members. These rights include communal land (ulayat land). In this study, has identification and attempts to describe the claims and the use of land in Jorong Landai, Nagari Harau, 50 Kota District, West Sumatra, by local communities and FMU of 50 Kota District. This research uses the descriptive qualitative method. In the Jorong Landai with a total area of 1388 Ha with each has ulayat area as follows: Bodi: 344 Ha, Pitopang 477 Ha, Sambilan 135 Ha and Melayu 427 Ha. The clan has used the ulayat land of 198,02 Ha for settlement, rice field, and gambir fields. The new boundaries for the area protected forest in Jorong Landai make overlapping claims of 57,01 Ha. Overlapping claims land use makes the activities local communities like blocked in their own land by the government. The primary forest in Jorong Landai of 1051 Ha (267 Ha in APL/Ulayat land and 784 Ha in protection forest). Secondary forest of 63,6 Ha (in APL/Ulayat land of 56,5 Ha and 7,1 Ha in protection forest).